FORMATION OF CIVIC COMPETENCIES IN HIGHER EDUCATION STUDENTS IN THE CONTEXT OF WAR - Любохинець, Лариса; Танассієнко, Наталія; Красильникова, Ганна (SWorldJournal, 2026)
The study provides a comprehensive analysis of the features of forming civic competencies of higher education students in Ukraine under wartime conditions. The transformation of the social role of higher education institutions is substantiated, as in the